2022
DOI: 10.1016/j.xplc.2021.100266
|View full text |Cite
|
Sign up to set email alerts
|

Advances in proteome-wide analysis of plant lysine acetylation

Abstract: Lysine acetylation (LysAc) is a conserved and important post-translational modification (PTM) that plays a key role in plant physiological and metabolic processes. Based on advances in Lys-acetylated protein immunoenrichment and mass-spectrometric technology, LysAc proteomics studies have been performed in many species. Such studies have made substantial contributions to our understanding of plant LysAc, revealing that Lys-acetylated histones and nonhistones are involved in a broad spectrum of plant cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 154 publications
(351 reference statements)
2
13
0
Order By: Relevance
“…Four histone proteins, including two histone H2A (Cd4A1G007030.1 and Cd4A1G023750.1), one histone H2B (Cd2A2G026820.1) and one histone 4 (Cd7A1G012090.1), are known to participate in gene expression regulation in plant growth and development (Fig. S 6 ; Table S 10 ) [ 43 ]. Acetylation of the four histone proteins at conserved lysine sites might be important for fast organ growth in the three grasses; however, the detailed regulatory functions of other conserved acetylated and succinylated proteins are unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four histone proteins, including two histone H2A (Cd4A1G007030.1 and Cd4A1G023750.1), one histone H2B (Cd2A2G026820.1) and one histone 4 (Cd7A1G012090.1), are known to participate in gene expression regulation in plant growth and development (Fig. S 6 ; Table S 10 ) [ 43 ]. Acetylation of the four histone proteins at conserved lysine sites might be important for fast organ growth in the three grasses; however, the detailed regulatory functions of other conserved acetylated and succinylated proteins are unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Our analyses successfully identified thousands of lysine acetylation modifications and hundreds of lysine succinylation modifications in fast-growing stolons of bermudagrass, however, many acetylated proteins and succinylated proteins possibly having important functions might not be determined due to their low abundance or poor reactivity with the affinity antibodies [ 43 ]. On the other hand, many studies have revealed that both acetylation and succinylation modifications exist in very low stoichiometries [ 5 , 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These have revealed a large number of potential key regulators of Pi homeostasis in plants, especially in Arabidopsis thaliana ( Thibaud et al, 2010 ; Woo et al, 2012 ) and rice ( Secco et al, 2013 ; Gho et al, 2018 ). Protein phosphorylation and succinylation are the two most important PTMs for regulating multiple biological processes in plants ( Nakagami et al, 2010 ; Xia et al, 2022 ). The recent developments of high-resolution mass spectrometry, antibody based affinity enrichment proteomic technology, and powerful bioinformatic tools have substantially contributed to the global analysis of protein phosphorylation and succinylation in barley.…”
Section: Discussionmentioning
confidence: 99%
“…Protein acetylation is a ubiquitous PTM, found in both eukaryotes and prokaryotes, and is involved in various key cellular processes [ 3 , 69 ]. Expression, biosynthesis and secretion of pathogenic factors in pathogens are regulated by protein acetylation during the interaction between pathogens and host plants [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysine-ε-acetylation (Kac) is a conserved post-translational modification (PTM) that was first discovered on histone proteins in 1964 [ 1 ], and occurs widely on non-histone in distinct organisms [ 2 , 3 ]. A few studies showed that Kac of non-histone is involved in the regulation of a range of biological processes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%